1996
DOI: 10.1046/j.1365-2036.1996.50192000.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose famotidine and ranitidine as single post‐prandial doses: a three‐period placebo‐controlled comparative trial

Abstract: We conclude that both famotidine 10 mg and ranitidine 75 mg significantly raise intragastric pH when given as single post-prandial doses. Famotidine 10 mg may have a greater effect than ranitidine elixir 75 mg over the 5-9-h period after dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
4
12
0
Order By: Relevance
“…As almost all studies regarding tolerance have involved subjects receiving long‐term ranitidine, information concerning this phenomenon with other H2RA is lacking. Famotidine has been reported to show a stronger and longer‐lasting acid‐suppressing effect than ranitidine and is the most potent H2RA currently used for clinical purposes 14–17 . Conflicting results have been reported concerning tolerance during famotidine administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As almost all studies regarding tolerance have involved subjects receiving long‐term ranitidine, information concerning this phenomenon with other H2RA is lacking. Famotidine has been reported to show a stronger and longer‐lasting acid‐suppressing effect than ranitidine and is the most potent H2RA currently used for clinical purposes 14–17 . Conflicting results have been reported concerning tolerance during famotidine administration.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few clinically available data concerning tolerance to other H2RA. Famotidine is a more recently developed H2RA that is reported to have stronger acid‐suppressing activity than ranitidine 14–17 . There have been conflicting results concerning the development of tolerance to famotidine treatment 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This is at variance with the Reilly study which reported that famotidine 10 mg was superior to ranitidine 75 mg liquid. 7 This discordance could be attributed to methodological differences as the Reilly study was performed by automated pH-metry. Despite studies which suggest pharmacodynamic equivalence, it is more likely that the superiority of the famotidine 10 mg tablet was due to the decreased bioavailability of the ranitidine 75 mg liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Over-the-counter H2RAs doses (ranitidine 75 mg, famotidine 10 mg), are less than those listed in the prescription product insert, however, at these doses they are effective in reducing overnight gastric acidity for 12 h [61], as well as blunting the food-stimulated gastric response [62,63]. They are also effective in the treatment of symptomatic GERD [47].…”
Section: Drugs Modulating Gastric Acidmentioning
confidence: 99%